Ex-situ synthesis of B4C and MgAl2O4 incorporated waste polystyrene (wPS) composites with improved thermal and mechanical properties - Ahmad, Waqas; Fida, Sadia; Ahmad, Imtiaz; Tariq, Razia; Mohamed Jan, Badrul; Hussain, Fida; Kenanakis, George; Ikram, Rabia (Springer Nature, 2024)
Boron carbide (B4C) and magnesium aluminate (MgAl2O4) incorporated waste polystyrene (wPS) based composites were prepared at various ratios i.e., 5–20% of the filler. Based on the fabricated composites, samples with 20% B4C, 5% MgAl2O4 and 15:10% B4C:MgAl2O4 exhibited improved mechanical and thermal properties. The tensile strength and young modulus of the composites was increased to 2622.5 and 27.931 MPa for 20%B4C, 2266.8 and 19.39 MPa for 5% MgAl2O4, 2719.4 and 21 MPa for 15:10% B4C:MgAl2O4 from that of 2232 and 10 MPa of wPS, respectively. TGA results showed that the temperature for 50% weight loss of wPS (337 °C) increased to 404 °C, 390 oC and 394 oC for wPS-B4C:20%, wPS-MgAl2O4:5% and wPS-B4C-MgAl2O4:15:10% composite, respectively. Their corresponding glass transition temperature increased from 79.65 °C to 265.6 °C, 291.19 oC and 302.5 oC for wPS-B4C:20%, wPS-MgAl2O4:5%, and wPS-B4C-MgAl2O4:15:10%, respectively. FTIR and SEM analysis concluded marginal changes in the surface topography and distribution of wPS particles upon the incorporation of B4C and MgAl2O4 fillers. XRD analysis indicated that the composite retained the crystalline configurations of original B4C and MgAl2O4, confirming the mere physical interaction of the filler with wPS. This study is focused on the cost-effective fabrication of various composites i.e., wPS-B4C, wPS-MgAl2O4 and wPS-B4C-MgAl2O4 with improved thermal stability and value-added mechanical performance which can be further envisioned of great prospects for industrial applications and devices. Graphical Abstract: (Figure presented.)